“Miniteachers”: technological and gamified program to enhance the motivation on primary school children - López Carrión, Vicente Amor (2021)
The design of educative programs created to develop the middle school students´ skills is a recurrent subject in educational literature. The aim of this article is to find evidences that support an enrichment program oriented to improve motivation and engagement in gifted students. The sample of sixty students (10-12 years old) was taken from a Peruvian middle school. The instrument used in this study were the School Attitude Assessment Survey-Revised (SAAS-R) (Siegle y McCoach, 2005) to measure motivation and a rubric revised by experts to measure engagement. Finally, the results are discussed and some improvements proposal are given.